Respostas

2014-04-30T01:57:06-03:00
 e um seguinte você iria usa assim:                         
 (2x+ 3)² 10 - (x + 4) (x - 2)                                      x = - b +- √Δ
                                                                                       2a      
4x + 9 = 10 - (x² - 2x - 4x + 8)                                 x = -(-10) +- √64
4x + 2x + 4x = 10 + 8 - 9 = x²                                          2.1
           10x = 9 = x²                                              x = 10 +- 8
x² - 10x + 9 = 0                                                              2
                                                                          x = 10 + 8 = 18 = 9
Δ = b² - 4 .a.c                                                                2        2
Δ = (-10) - 4 .1. 9                   S= { 9,1 }               x = 10 - 8 = 2 = 1
Δ = 100 - 36                                                                2       2
Δ = 64                                                                       

2 3 2